Effects of Jaw Clenching and Jaw Alignment Mouthpiece Use on Force Production During Vertical Jump and Isometric Clean Pull. Issue 1 (January 2018) - Allen, Charles R.; Fu, Yang-Chieh; Cazas-Moreno, Vanessa; Valliant, Melinda W.; Gdovin, Jacob R.; Williams, Charles C.; Garner, John C.
Abstract : Abstract: Allen, CR, Fu, Y-C, Cazas-Moreno, V, Valliant, MW, Gdovin, JR, Williams, CC, and Garner, JC. Effects of jaw clenching and jaw alignment mouthpiece use on force production during vertical jump and isometric clean pull. J Strength Cond Res 32(1): 237–243, 2018—This study examined the effects of jaw clenching, a self-adapted, jaw-repositioning mouthpiece on force production during maximum countermovement vertical jump and maximum isometric midthigh clean pull assessments in an attempt to determine any ergogenic effect attributable to clenching, jaw-repositioning mouthpiece use, or the combination of both. Thirty-six male subjects performed vertical jump and isometric clean pull assessments from a force platform under various mouthpiece and clench conditions. A 3 × 2 (mouthpiece × clench) repeated-measures analysis of variance was conducted to analyze each of the following force production variables for both assessments: peak force, normalized peak force, and rate of force development. In addition, jump height was analyzed for the vertical jump. Results revealed improvements in peak force ( F 1, 35 = 15.84, p ⩽ 0.001, = 0.31), normalized peak force ( F 1, 35 = 16.28, p ⩽ 0.001, = 0.32), and rate of force development ( F 1, 35 = 12.89, p = 0.001, = 0.27) during the isometric clean pull assessment when participants maximally clenched their jaw, regardless of mouthpiece condition. There were no statistically significant differences in jump height, peak force, normalized peak force, or rate of force development during the vertical jump for any treatment condition. This study supports previous research demonstrating that the implementation of remote voluntary contractions such as jaw clenching can lead to concurrent activation potentiation and a resulting ergogenic effect during activities involving and requiring high-force production.